2015
DOI: 10.1007/s11255-015-1073-2
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters can predict the extent of coronary artery disease in patients with end-stage renal disease

Abstract: Aside from the well-known traditional factors, NLR and MPV are independent predictors of the extent of CAD in patients with ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…Nonetheless, in this study a positive correlation was found in control group between these two parameters (33). In another study by Bal et al on patients with ESRD, they showed that MPV could predict the extent of coronary artery disease (44).…”
Section: Discussioncontrasting
confidence: 47%
“…Nonetheless, in this study a positive correlation was found in control group between these two parameters (33). In another study by Bal et al on patients with ESRD, they showed that MPV could predict the extent of coronary artery disease (44).…”
Section: Discussioncontrasting
confidence: 47%
“…It is inversely correlated with glomerular filtration rate. Two studies have found a link between high MPV and coronary heart disease [34,35]. A recent study of a national retrospective cohort of 149,000 chronic HD patients found a correlation between an increase in MPV and mortality [36] but not with cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…CAG was performed via the femoral approach using the Judkins technique according to Ohtake et al and Bal et al description [18,19]. The angiograms were evaluated by an experienced interventional cardiologist.…”
Section: Coronary Angiography (Cag) and Percutaneous Coronary Intervementioning
confidence: 99%